Tropical Foliage Plant Development: Breeding Techniques for Anthurium and Spathiphyllum - Richard J. Henny; Jianjun Chen; Terri A. Mellich (EDIS, 2008)
ENH-1102, a 4-page illustrated fact sheet by R.J. Henny, J. Chen, and T.A. Mellich, describes new techniques plant breeders can use to manipulate flowering and pollination in ornamental aroids for hybridization purposes. Includes references. Published by the UF Department of Environmental Horticulture, June 2008.